(untitled) ("Journal "U". Economy. Management. Finance.", 2021)
Investing is one of the easiest and smartest ways to generate income for both legal entities and individuals. The only difference is the size of the funds available for investment, the short-term goals of the investor, as well as the attitude to planning this action. For individuals, the priority is the financial market, since the threshold for entering it is the lowest and it does not require specific knowledge.